Morphological identification of two root-knot nematode species occurring in vegetable crops of Zhejiang, China - ZHAO Lei; GUO Kai; HONG Wen-ying; ZHENG Jing-wu (浙江大学学报. 农业与生命科学版, 2010)
During 2007 to 2009, an extensive survey and morphological identification on root-knot nematodes, Meloidogyne spp., occurring in vegetable crops of Zhejiang, China, were carried out. Based on diagnostic characters and morphometrics of females, males, and second-stage juveniles, especially the perineal patterns of female, two species were identified, i.e. M. incognita and M. javanica, in which M. incognita was the preponderant species, widely distributed in vegetable crops of Zhejiang, whereas M. javanica was only found in Wenzhou of Zhejiang, and this was the first record of the species in Zhejiang.